Prospective evaluation of a combination of fungal biomarkers for the diagnosis of invasive fungal disease in high-risk haematology patients - Hammarström, Helena; Heußel, Claus Peter (Mycoses, 2018)
We prospectively evaluated a combination of fungal biomarkers in adult haematology patients with focus on their clinical utility at different time points during the course of infection. In total, 135 patients were monitored once to twice weekly for serum (1-3)-ß-d-glucan (BG), galactomannan (GM), bis-methyl-gliotoxin and urinary d-arabinitol/l-arabinitol ratio. In all, 13 cases with proven or probable invasive fungal disease (IFD) were identified. The sensitivity of BG and GM at the time of diagnosis (TOD) was low, but within 2 weeks from the TOD the sensitivity of BG was 92%. BG >800 pg/mL was highly specific for IFD. At a pre-test probability of 12%, both BG and GM had negative predictive values (NPV) >0.9 but low positive predictive values (PPV). In a subgroup analysis of patients with clinically suspected IFD (pre-test probability of 35%), the NPV was lower, but the PPV for BG was 0.86 at cut-off 160 pg/mL. Among IFD patients, 91% had patterns of consecutively positive and increasing BG levels. Bis-methyl-gliotoxin was undetectable in 15 patients with proven, probable and possible IA. To conclude, BG was the superior fungal marker for IFD diagnosis. Quantification above the limit of detection and graphical evaluation of the pattern of dynamics are warranted in the interpretation of BG results.
Gesehen am 21.08.2019